Estimated Instantaneous Airborne Traffic in the North Atlantic. - Dunmire,Chester E. (1970)
Considerable study is currently being devoted to satellite applications for aviation services in oceanic areas. A principal influence on satellite sizing and related system design is the nature of air traffic to be served during busy operating periods throughout the area of satellite coverage. The purpose of this report is to develop a data base, for near peak conditions during 1969, in terms of instantaneous airborne count (IAC) in the North Atlantic airspace considered most practical for first generation operational satellite systems. This data base is then used along with internationally agreed annual traffic growth forecasts to provide a projection of expected near peak IAC2 for each year through 1979. (Author) Previously announced as N72-12585.